The role of nonbank financial institutions in the monetary transmission mechanism: Theory and evidence - Sung-Eun Yu (The University of Utah, Department of Economics, 2017)
Nonbank financial institutions (NBFIs) have substantially increased their market share since 1980s. In spite of the growing importance of NBFIs, they have received much less attention in the monetary transmission mechanism. This paper examines if monetary policy affects NBFIs in the similar way as banks. First, I theoretically explain how monetary policy influences the loan supply of all financial intermediaries (banks and NBFIs) through changes in their net worth. Then, I empirically test whether these two kinds of lending institutions decrease their net worth and the intermediated loans in response to a tight monetary shock. I find that, at the statistically significant level, NBFIs shrink their net worth and a type of loan, especially C&I loans - but not all types of loans decrease, as predicted - in the same way as banks. In particular, NBFIs' C&I loans "decrease" substantially in the beginning periods; however, NBFIs' mortgages and consumer credit "increase" in the middle periods, showing a statistically significant level. These evidences suggest that the theoretical explanation is, at least, consistent with the evidence of C&I loans - but not mortgages and consumer loans. One possible explanation is that, while banks reject mortgages and consumer loans, NBFIs may increase mortgages and consumer loans by picking up the demand for these two types of loans.
Keywords: E51; E52; E58; 330; monetary policy; nonbank financial institutions; net worth; loan supply